A new combination of a prebiotic and postbiotic mitigates immunosenescence in vaccinated healthy senior dogs - Wambacq, Wendy A.; Apper, Emmanuelle; Le Bourgot, Cindy; Barbe, Florence; Lyu, Yang; Pelst, Michael; Broeckx, Bart J. G.; Devriendt, Bert; Cox, Eric; Hesta, Myriam (Frontiers in Veterinary Science, 2024)
IntroductionElderly dogs often suffer from chronic diseases, in part attributed to immunosenescence, characterized by reduced blood CD4+ T cells (helper T cells) and elevation in the CD8+ T cells subset (cytotoxic T cells). Studies conducted in adult dogs suggested that supplementing short chain fructo-oligosaccharides (scFOS) or postbiotics derived from yeasts may positively influence the immune response. The aim of the current study was to investigate whether dietary supplementation with a combination of scFOS with a new yeast postbiotic (Profeed ADVANCED® called scFOS+) could have a positive influence on the immune status of senior dogs subjected to an immune challenge (Lyme disease vaccination).MethodsTo this end, 22 healthy senior client-owned dogs were divided into two groups: one group received a placebo diet without scFOS+ and the other group the basal diet supplemented with 1.1% scFOS+. In order to assess immune function, complete blood count, serum acute phase proteins, immunoglobulins, cytokines, T-cell subsets and antibody secreting cells were analyzed. Furthermore, faecal score and pH were recorded.Results and discussionDogs fed the scFOS+ supplement had decreased total serum IgA concentrations (p < 0.01), which might suggest a more local IgA response in agreement with what was previously found when adult dogs were supplemented with β-1, 3/1, 6-glucan, a yeast-based product. More importantly, the present study demonstrated that feeding 1.1% scFOS+ to healthy senior dogs increased the CD4+:CD8+ T-cell (Helper:Cytotoxic T cell) ratio (p < 0.001) during and after vaccination against Lyme disease. Combining scFOS and yeast-derived postbiotics in the diet can therefore counter certain characteristics of T-cell immunosenescence in dogs.